2021
DOI: 10.1007/s10826-021-01951-1
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Home Environment and Quality of Life in Children and Adolescents in Hangzhou City, China

Abstract: To investigate the influence of the home environment, defined as family socioeconomic status (SES) (parent education level, household income), student resource-mediated SES (access to nutritional resources and cognitively stimulating experiences), reading ability, and difficulty with homework on quality of life in children and adolescents residing in urban and suburban areas in Hangzhou City, Zhejiang Province, China. This study included 3200 Grade 3–6 students from 8 elementary schools in Hangzhou City. Asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The results of this study are in line with the theory of adolescent socialization which states that adolescents begin to expand their psychosocial development into a wide scope ( Huang et al., 2021 ; Meter et al., 2019 ). The family is the first social environment that individuals have encountered since they were born into the world ( Hanani, 2019 ; Jenkins et al., 2018 ; Sanner and Neece, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results of this study are in line with the theory of adolescent socialization which states that adolescents begin to expand their psychosocial development into a wide scope ( Huang et al., 2021 ; Meter et al., 2019 ). The family is the first social environment that individuals have encountered since they were born into the world ( Hanani, 2019 ; Jenkins et al., 2018 ; Sanner and Neece, 2018 ).…”
Section: Discussionsupporting
confidence: 87%
“…The study also provided the discovery that parents who work together in parenting make adolescents feel safe. Parents who can carry out good cooperation will have an impact on good mental and psychosocial development in adolescents ( Fang, 2018 ; Huang et al., 2021 ). Cooperation in this case includes, for example, the father who acts as the head of the household, but still accompanies the child in learning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They mentioned that: This study's findings are consistent with previous research (for example: Banstola et al, 2020;Sugiarti et al, 2021;Tulip et al, 2020;Smith-Adcock et al, 2019), which found that the family climate, as mediated by parenting, plays an important role in the development of character in adolescents. Other experts, such as Huang et al (2021) as well as Lin and Chiao (2020), have argued that family members will display diverse personalities influenced by their parents at home, which will be strengthened as they grow older. Hart et al (2019) also stated that this influence will grow as their social circle expands, regardless of whether they choose peace, value variety, or demonstrate self-awareness of the social context.…”
Section: Character Buildingmentioning
confidence: 99%